Optimization of dye-sensitized solar cells with polyacrylonitrile gel polymer electrolytes blended with alkyl ammonium salts and ionic liquids / Faisal Islam Chowdhury - Faisal Islam , Chowdhury (2018)
Gel polymer electrolytes (GPEs) consisting of polyacrylonitrile (PAN) polymer, ethylene carbonate (EC) and propylene carbonate (PC) plasticizers and different compositions of quaternary ammonium iodide salt (tetrapropylamonium iodide, TPAI or tetrabutylamonium iodide, TBAI) have been prepared and investigated. To understand the nature of GPEs containing different quaternary ammonium iodide salts (TPAI or TBAI) and/or room temperature ionic liquids (1-propyl-3-methyl imidazolium iodide, PMII or 1-butyl-3-methyl imidazolium iodide, BMII), four sets of GPEs: (i) PAN:EC:PC:TPAI:I2, (ii) PAN:EC:PC:TBAI:I2, (iii) PAN:EC:PC:TPAI:PMII:I2 and (iv) PAN:EC:PC:TPAI:BMII:I2 have been prepared and investigated. To characterize the GPEs, electrochemical impedance spectroscopy (EIS), linear sweep voltammetry (LSV) and X-ray diffraction (XRD) techniques have been utilized. The DSSCs fabricated with these electrolytes have been characterized using J-V, IPCE, IMPS and IMVS techniques. The GPE with TPAI shows higher conductivity (3.62×10-3 S.cm-1) than that of TBAI (3.46×10-3 S.cm-1). For further improvement of electrolyte performance TPAI based GPE has been chosen to be added with PMII and BMII ionic liquids. The conductivity of PMII (5.90×10-3 S.cm-1) > BMII (3.54×10-3 S.cm-1). The activation energy for ion conduction, Ea decreases accordingly as: TBAI (12.59 kJ/mol) > TPAI (10.09 kJ/mol) > TPAI+BMII (6.20 kJ/mol) > TPAI+PMII (6.14 kJ/mol). The values of Jlim,